Immune pathogenesis of idiopathic granulomatous mastitis: from etiology toward therapeutic approaches - Wang, Xiaoli; He, Xiujing; Liu, Junzhi; Zhang, Haiyan; Wan, Hangyu; Luo, Jing; Yang, Jiqiao (Frontiers in Immunology, 2024)
Idiopathic granulomatous mastitis (IGM) is a chronic, noncancerous inflammatory breast disorder with an unknown cause, posing significant challenges to the quality of life due to its high refractoriness and local aggressiveness. The typical symptoms of IGM include a firm, tender breast mass, skin redness, and mastalgia; others may include swelling, fistula, abscess (often without fever), nipple retraction, and peau d'orange appearance. IGM often mimics breast abscesses or malignancies, particularly inflammatory breast cancer, the definite diagnosis relies on core needle biopsy and histopathological examination as a result of the absent standardized treatment options, inconsistent patient response, and the unknown mechanism of the disease. The prevailing etiological theory suggests that IGM is an autoimmune disease, as some patients respond well to steroid treatment. Additionally, the presence of concurrent erythema nodosum or other autoimmune conditions supports the autoimmune nature of the disease. Based on current knowledge, this review aims to elucidate the autoimmune-favored features of IGM and explore its potential etiologies. Furthermore, we discuss the immune-mediated pathogenesis of IGM using existing research and propose immunotherapeutic strategies for managing this condition.